Revision of Heteroscelis Latreille, 1829 (Heteroptera: Pentatomidae: Asopinae) with the description of a new species from Colombia - Sampaio, Vinicius Gomes; Roell, Talita; Campos, Luiz Alexandre (Zootaxa, 2023)
The Asopinae comprises about 300 species and 63 genera of predatory stinkbugs, of which around 100 species and 23 genera occur in the Neotropical region. The species of the Neotropical genus Heteroscelis Latreille, 1829 are easily recognized by the small size, vivid and often iridescent colors, the elongated head, and the foretibial foliaceous expansions. In this work we provide a taxonomic revision of Heteroscelis. The genus and its four known species are redescribed, and one new species from Colombia, Heteroscelis vandembergi Sampaio & Campos, sp.nov., is proposed. A distribution map, and a key to the species of Heteroscelis are presented.